Combined effects of the serum IgA/C3 ratio and glomerular C3 staining on the renal outcome in adult IgA nephropathy. - Dandan Yang; Gaiqin Pei; Siqing Wang; Aiya Qin; Yi Tang; Wei Qin (Karger Publishers, 2024)
Introduction: The aim of this study was to evaluate the predictive value of the serum IgA/C3 ratio and glomerular C3 deposits in kidney biopsy in adult IgA nephropathy. Methods: The study included 718 adult IgAN patients diagnosed based on kidney biopsy. Patients without corticosteroids or immunosuppressive drugs >1 month were regularly followed up for at least 1 year or until the study endpoint. The optimum serum IgA/C3 ratio was calculated by the AUROC-based cutoff ratio. Proteinuria, creatinine, eGFR, serum IgA, and serum C3 were evaluated at baseline. Kidney biopsy was categorized using the Oxford classification, with a calculation of the MEST-C score. The degree of glomerular C3 staining was semiquantitatively determined (Grade 0, no or trace; Grade 1, mild; Grade 2, moderate; Grade 3, marked) by immunofluorescence microscopy. The patients were divided into four groups by the serum IgA/C3 ratio and glomerular C3 staining. Results: The baseline data suggested that when the serum IgA/C3 ratio was at the same level, patients with a high glomerular C3 staining score (≥2) always had mesangial proliferation, segmental glomerulosclerosis and tubular atrophy/interstitial fibrosis (Group 1 vs Group 2; Group 3 vs Group 4). When glomerular C3 staining was at the same level, proteinuria was significantly higher in patients with serum IgA/C3<2.806 (Group 1 vs Group 3; Group 2 vs Group 4), which was contrary to previous studies that have suggested that the serum level of IgA/C3 was associated with disease severity. Hence, this study set out to investigate the combined effects of the serum IgA/C3 ratio and glomerular C3 staining on the renal outcome in adult IgA nephropathy. Renal survival analysis indicated that serum IgA/C3 ≥2.806 and glomerular C3 staining ≥2 (Group 1) may be correlated with a poorer prognosis, especially in different clinicopathological characteristics of IgAN patients based on the subgroup analysis. Multivariate Cox analysis demonstrated that hypertension, serum creatinine, CKD stage, T1/2 and C3 staining were independent predictive factors of renal survival. Conclusions: The combination of serum IgA/C3 and C3 staining may contribute to improved optimization of the prognostic model in IgAN patients, especially patients with different sexes and degrees of disease. However, further study is required for validation in the future.